Development of The Jungle Adventure Game Media to Stimulate Concentration in Early Childhood - Diana Wulandari; Intan Prastihastari Wijaya; Linda Dwiyanti (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
This study aims to develop “The Jungle Adventure” game-based learning material to stimulate concentration in early childhood. The study employed the Research and Development (R&D) method, which includes needs analysis, information gathering, product design, validation, testing, and product revision. The research subjects consisted of one subject matter expert, one media expert, two teachers from Kindergarten Class A2, and 11 children aged 3–4 years at Kindergarten Class A2 of Labschool UN PGRI Kediri. Data collection techniques included observation, interviews, documentation, an expert validation questionnaire, and a teacher practicality questionnaire. The data were analyzed qualitatively and quantitatively using percentages. The results showed that the media received 100% subject matter expert validation and 95% media expert validation, both categorized as “highly valid.” The results of the teacher practicality test reached 92.5%, categorized as “highly practical.” A limited pilot test showed positive responses from children toward the media as well as an increase in children’s concentration, as indicated by an increase in the “Developing as Expected” and “Developing Very Well” categories. Thus, the “The Jungle Adventure” media is deemed valid, practical, and suitable for use in stimulating concentration in early childhood.